Antielastasic activity of antistressants in bone tissue of rats after stress - Pavlenko, K. (Journal of Education, Health and Sport, 2026)
Background. Stress causes the development of post-stress pathological reactions, which culminate in dysmetabolic disorders, against the background of which most diseases of humans and animals develop. Bone tissue has been found to be one of the most sensitive organs and tissues to the effects of dysmetabolic syndrome. Aim. Study of the effect of stress on the activity of the proteolytic enzyme elastase in bone tissue and determination of the possibility of preventing elastase activation using anti-stress agents. Methods. Stress was induced in rats by holding the animals at −20 °C for 30 minutes and elastase activity was investigated on the 4th day after stress. Antioxidant preparations EkSoVit, Quercetin and ascorbic acid were used as anti-stressors, which were administered into the oral cavity 3 days before stress and 3 days after stress in the form of an oral gel in doses (mg/kg): EkSoVit 0.43 and 1.07, Quercetin 0.128 and 0.257 and ascorbic acid 0.257. Results. In rats without stress, the elastase activity in the femur was (μk-kat/kg) 6.66; in rats after stress 9.61; in rats with stress that received EkSoVit, 8.16 and 6.90; in rats with stress that received quercetin, 7.20 and 5.60; in rats with stress that received ascorbic acid, 7.20. The antielastase activity in vivo was: EkSoVit – 49.15 and 126.05; quercetin – 112.10 and 135.93 and ascorbic acid – 81.63. The antielastase efficacy of antistressants was after conversion of antielastase activity to a dose of 1 g/kg: for EkSoVit 114.3 and 117.8; for quercetin 875.8 and 528.9; for ascorbic acid 317.8. Conclusion. After stress, the activity of the proteolytic enzyme elastase increases in bone tissue. The use of anti-stress agents with antioxidant action significantly prevents the activation of elastase. The most effective anti-elastase drug was quercetin (vitamin P).